A new species of crayfish in the genus Orconectes (Decapoda: Cambaridae) from the Tennessee River Drainage with comments on and key to members of the O. juvenilis Species Complex - Taylor, Christopher A.; Rhoden, Cody M.; Schuster, Guenter A. (Zootaxa, 2016)
The crayfish subgenus Procericambarus (genus Orconectes) found in the Eastern Highlands of the United States represents a rich assemblage of stream-dwelling macroinvertebrates. While the taxonomic status and distribution of its members were clarified in a previous study, newly diagnosed characters and newly collected specimens warranted a revision to previous hypotheses of Procericambarus membership in the southeastern United States. Using morphological characters, we describe herein a new species of crayfish occurring in the Tennessee River drainage of northern Alabama and southwestern Tennessee. We also provide a revised key for the identification of members of O. juvenilis Species Complex.